Long-Term Functional Recovery after Severe Traumatic Brain Injury with Type II Diffuse Injury - Marcia Harumy Yoshikawa; Sérgio Brasil; Davi Jorge Fontoura Solla; Robson Luís Amorim; Daniel Augustin Godoy; Angelos Kolias; Wellingson Silva Paiva (Neurotrauma Reports)
This study aims to describe the late clinical outcomes of patients with severe traumatic brain injury (sTBI) and the risk factors associated with it. Patients were enrolled between April 2012 and January 2015 and followed until January 2022. The inclusion criteria were age 16–65 years, Glasgow Coma Scale ≤8 on admission, diagnosis of blunt TBI with Marshall diffuse injury type II on initial computerized tomography (CT), and alive at discharge. Clinical, laboratory, and radiological data from admission were collected. Glasgow Outcome Scale Extended (GOSE), Functional Independence Measure, and Zarit Burden Interview (ZBI) were assessed in the follow-up. Sixty-five patients were included, with a median follow-up time of 8 years. Nineteen (29.2%) patients had good recovery (GOSE 7–8), and 10 (15.3%) had moderate-to-severe sequelae (GOSE 4–6). Thirty-six (55.4%) patients died after discharge, and most of them in the first 3 months after discharge (n = 26; 72.2%). Despite the early mortality rate being the highest, the 6-month score is explained in the text (CRASH-CT) score on admission was not associated with death in the follow-up (p = 0.25). In the multivariate statistical analysis, only prothrombin time was associated with GOSE (p = 0.01). Twelve (41.3%) patients were independent for basic activities of daily living, and the most common cause of dependence was memory impairment (n = 12; 41.3%). The median ZBI score reported by caregivers was 23.5 (range 5–48), indicating mild overload. In this study, patients with sTBI sustaining Marshall II lesions had a significant mortality rate after discharge, and we found coagulation impairment as a potential predictor of poor outcomes. Around 30% experienced functional dependence and inability to return to social and work activities. Current instruments used to predict outcomes of TBI patients had poor predictive performance in this low- and middle-income country population, suggesting the need for new models to properly guide clinical decision-making and counseling family members.